Clinical Performance of Minimally Invasive Monolithic Ultratranslucent Zirconia Veneers: A Case Series up to Five Years of Follow-up - Silva, N. R.; Araújo, Gm de; Moura, Dmd; Araújo, Lnm de; Gurgel, Bc de Vasconcelos; Melo, R. M. [UNESP]; Bottino, M. A. [UNESP]; Özcan, M.; Zhang, Y.; Souza, Roa (Operative Dentistry, 2023)
There is a lack of reports in the literature on the long-term clinical performance of ultratranslucent zirconia, especially considering its use in manufacturing monolithic veneers. The purpose of this case series is to describe the aesthetic treatment steps of three patients with minimally invasive ultratranslucent zirconia veneers and to report the clinical findings up to five years. Three patients (woman: 2, man: 1; mean age: 30 years) unsatisfied with their dental aesthetics sought dental treatment. The treatment plan involved cementing ultratranslucent zirconia veneers. Air-abrasion was performed on the internal surface of zirconia with alumina particles coated by silica (silicatization), followed by silane and adhesive applications for the adhesive cementation. All veneers were adhesively cemented to enamel with resin cement (Variolink Esthetic, Ivoclar). The patients were clinically evaluated annually considering the Ryge modified/ California Dental Association criteria. After a mean follow-up of 4.33 years (4-5 years), a survival rate of 100% was detected for the 28 minimally invasive ultratranslucent zirconia veneers cemented in the 3 patients. There were no absolute failures such as debonding, veneer fracture, or secondary caries. Superficial marginal discoloration was observed in one element (maxillary left lateral incisor) of one patient. Ultratranslucent zirconia is a viable option for manufacturing veneers due to its excellent clinical performance and longevity. However, further long-term clinical studies are essential to consolidate this material as an option for esthetic restorations.